Large scale fluctuations of the Continental Tropical Convergence Zone (CTCZ) during pilot CTCZ phase-2009 and the evolution of monsoon drought in 2009 - SIKKA, D. R.; TYAGI, AJIT; RAM, L. C. (MAUSAM, 2010)
Summer monsoon season of the year 2009 resulted in a major drought on the scale of India with rainfall deficiency of 23% from the normal. This was the monsoon season when a pilot phase of the programme Continental Tropical Convergence Zone (CTCZ), a planned multiyear programme to understand the complex interactions among the land, ocean, atmosphere, biosphere components of the regional monsoon climate system, was undertaken. The paper attempts to document the major features in the evolution of monsoon 2009 and provides a preliminary diagnosis of the causes for monsoon drought.